INTEGRATION AND DISINTEGRATION IN ISTANBUL CENTRAL AREA: THINKING OVER THE RESULTS OF THE 15TH ISOCARP YOUNG PLANNING PROFESSIONALS WORKSHOP - Evren, Yigit (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2007)
The central area of Istanbul has been loosing a balance between its functions and population. Since the 1990s some of the central neighbourhoods have been witnessing a significant decrease in their residential population due to the ongoing transformation process from residential use to services. Some neighbourhoods, however, have been deteriorated and occupied by low income migrants. Yet some of those previously deteriorated areas have been revitalised by the new elite and become gentrified. Meanwhile, as the pace of globalisation increases, the pressure on the central area from developers who attempt to build iconic projects increases. From a planning perspective, this is a two fold integration versus disintegration problem. On the one hand, within the central area, planners face a challenge of reaching a balance of fragmented city since the central area of Istanbul has become a patchwork of various disintegrated functions. With respect to the relationship between the central area and the metropolis, on the other hand, most of those so-called iconic flagship projects are put on the agenda with no regard to the existing local plans and identities. Thus, such initiatives, threaten the image and the functioning of the city. This paper aims to discuss the results of the 15(th) ISoCaRP Young Planning Professionals Workshop, which was held in Istanbul in 2006 on the abovementioned topic.
Keywords: Istanbul; central area; integration; disintegration; ISoCaRP; Architecture